Significance of lymphocytic infiltrate in the development of hypothyroidism following thyroidectomy for benign thyroid lesions. - Quadros, Dr. Gloria Venissa; Saldanha, Dr. Prema; T. P., Ms. Mandara (International Journal of Innovative Research in Medical Science, 2018)
Multinodular Goitre (MNG) is a common disorder and the incidence of hypothyroidism following thyroidectomy varies in different studies. Of the many factors which determine the post-operative thyroid hypofunction, the presence of an inflammatory infiltrate in the thyroid gland may have a significant role. The objective was to study the association of post-operative hypothyroidism and lymphocytic infiltration in the thyroid gland. This was a retrospective study of patients who underwent thyroidectomy. Detection of hypothyroidism was based on thyroid function test values. The lymphocytic infiltrate within the thyroid gland was graded as 0,1,2,3 & 4. Correlations between the grade of lymphocytic infiltration and the patient’s age, type of surgery and hypothyroid status was assessed. In our patients, 59 (57.2%) cases developed hypothyroidism post-operatively, of which 72.3% had a high lymphocytic grade. Out of the cases having a high lymphocytic infiltration who developed hypothyroidism, 63.8% were above 40 years of age. There was statistically significant correlation between the grade of lymphocytic infiltration and hypothyroid status post-operatively (p = 0.017). This suggests its role in the progressive development of post-operative hypothyroidism.